2003
DOI: 10.1136/bjo.87.9.1154
|View full text |Cite
|
Sign up to set email alerts
|

Nestin positive cells in adult human retina and in epiretinal membranes

Abstract: Background/aim: Nestin is an intermediate filament marker for neural progenitor cells. The authors aimed to identify nestin positive cells in adult human retina and within surgically removed epiretinal membranes. Methods: Adult human retina and epiretinal membranes were studied. Tissue was fixed and processed for semithin sections or whole mount preparations for immunohistochemical detection of nestin and glial fibrillary acidic protein (GFAP) expression. Results: Nestin positive cells are most prominent at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 32 publications
(25 reference statements)
3
51
0
7
Order By: Relevance
“…This suggests that undifferentiated stem cells of the fovea differentiate and grow into glial cells. In fact, nestin-positive cells have been found in epiretinal membranes [12].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that undifferentiated stem cells of the fovea differentiate and grow into glial cells. In fact, nestin-positive cells have been found in epiretinal membranes [12].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adult human retina have closely examined the expression of the neural progenitor marker nestin in the retina. Nestin is expressed in some cells at the junction of the neural retina and the ciliary body, which suggests that a remnant of the CMZ may remain in humans (Mayer et al, 2003). Thus, it appears that the CMZ has made a progressively smaller contribution to the growth of the retina in the evolution of higher vertebrates (Fig.…”
Section: E F G Hmentioning
confidence: 99%
“…9,41,42 We have noted the expression of nestin (embryonic type VI intermediate filament) in adult human retina. 43 Nestin is expressed during development and is a signature of mitotically active progenitor cells, particularly neuronal, within cells in the subventricular zone of the CNS. The observation of nestin-positive cells in CMZ as well as in radial cells within the retina infers the presence of progenitor cell populations within the retina as well as that of cells capable of directing migration of cells within the tissue towards cell renewal.…”
Section: Retinal Progenitor Cellsmentioning
confidence: 99%
“…46,47 Further, our initial observations demonstrated that cells from epiretinal membranes of surgical specimens expressed nestin. 43 We have isolated a population of nestin-positive CD133 þ CD90 À cells from adult human retina that show, albeit small, a significant capacity to divide and generate neurospheres and differentiate into neurones, glia, and photoreceptors (Carter et al, unpublished data). These cells are maintained by LIF (leukaemia inhibitory factor) in a proliferative but undifferentiated state.…”
Section: Retinal Progenitor Cellsmentioning
confidence: 99%